Governing the souls of young women: exploring the perspectives of mothers on parenting in the age of sexualisation. Issue 3 (3rd May 2016) - Howard, Chris; Hallam, Jenny; Brady, Katie
Abstract : The sexualisation of young women has emerged as a growing concern within contemporary western cultures. This has provoked adult anxieties that young women are growing up too fast by adopting inappropriate sexual practices and subjectivities. Psychological discourses have dominated, which position sexualisation as a corrupting force that infects the 'true self' of young women, so they develop in abnormal ways. This in turn allows psychological practices to govern how to parent against sexualisation within families. To explore this further, six mothers each with daughters aged between 8 and 12 took part in one to one semi-structured interviews designed to explore how they conceptualised and parented against the early sexualisation of young women. A Foucauldian inspired discourse analysis was employed, which suggested that the mother's talk was situated within a psychological discourse. This enabled sexualisation to be positioned as a corrupting force that disrupted the natural development of young women through deviant bodily practices (e.g. consuming sexualised goods), which prevented them from becoming their 'true self'. Through the disciplinary gaze of psychology, class inequalities were reproduced where working class families were construed as 'chavs' who were bad parents and a site of contagion for sexualisation.